If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.39 = 3x Solving 0.39 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 0.39 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0.39 + -3x = 0 Add '-0.39' to each side of the equation. 0.39 + -0.39 + -3x = 0 + -0.39 Combine like terms: 0.39 + -0.39 = 0.00 0.00 + -3x = 0 + -0.39 -3x = 0 + -0.39 Combine like terms: 0 + -0.39 = -0.39 -3x = -0.39 Divide each side by '-3'. x = 0.13 Simplifying x = 0.13
| 15=6v-7 | | 0=-2x^2-12x+1 | | x^2+8x+33=0 | | 5x+6789y= | | -2x^2-12x+1=y | | -7w+2w= | | 3(x+2)=3(x+5) | | 3i-6= | | 500=(r+8)3 | | 12u+v+16u+7v= | | 500=3t | | 12-4x=1-x | | 35+12x=95 | | -5(-1.5+0.25y)=21 | | 10N-1=89 | | -2x^2-12x+1=0 | | 10x+160=300 | | 90=b+15(b+2)+15+2b-9 | | 30-4x=12-10x | | 5b-2=2b+16 | | (2x+3x-6)+(x^2-18x+6)= | | 118-2g=4g | | x^6+81y^3=0 | | y=50x-550 | | 2x^2+(m-1)*y^2-2mx+4y-1=0 | | 2(3a-1)=3(a-1) | | 8x^2-10=16x | | -t-(0.4)=-3 | | (7-3i)(8+4i)= | | 3(3a-4)=6 | | x^2-(441-84x+4x^2)=21 | | 180=x+x+54 |